1992
DOI: 10.1056/nejm199207093270205
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Alternative Hand-Washing Agents in Reducing Nosocomial Infections in Intensive Care Units

Abstract: A hand-disinfection system using an antimicrobial agent (chlorhexidine) reduces the rate of nosocomial infections more effectively than one using alcohol and soap. The improvement may be explained at least in part by better compliance with hand-washing instructions when chlorhexidine was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
153
0
9

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 466 publications
(166 citation statements)
references
References 39 publications
3
153
0
9
Order By: Relevance
“…Compliance rates for basic infection control measures, such as hand washing, have been reported to vary from 20% to 40%, but may be higher for well-motivated nursing and other medical staff (16)(17)(18). By using transmission data for VRE in an endemic setting, we estimate that the basic or case reproductive number R 0 , which provides a quantitative measure of transmission, lies in the range 3-4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compliance rates for basic infection control measures, such as hand washing, have been reported to vary from 20% to 40%, but may be higher for well-motivated nursing and other medical staff (16)(17)(18). By using transmission data for VRE in an endemic setting, we estimate that the basic or case reproductive number R 0 , which provides a quantitative measure of transmission, lies in the range 3-4.…”
Section: Discussionmentioning
confidence: 99%
“…Barrier precautions, such as the use of gowns and gloves, and hand washing serve to reduce the likelihood that HCWs will become contaminated with VRE (16)(17)(18). If the probability of compliance is P per patient contact, and precautions are 100% effective in removing VRE contamination, then HCWs have a reduced probability of transmitting VRE to their next patient.…”
Section: The Impact Of Infection Controlmentioning
confidence: 99%
“…Even if washing hands is 100% e¡ective, the threshold compliance rate can be very high for modest values of R 0 . Studies show reported compliance rates of 20^40% (Albert & Condie 1981;Simmons et al 1990;Doebbelling et al 1992). If R 0 is in excess of 1.25^1.67, hand-washing measures alone are unlikely to be su¤cient for controlling endemic transmission.…”
Section: (I) Hand-washingmentioning
confidence: 99%
“…Semmelweis decreased the rate of maternal mortality from 22% to 3% by requiring the physicians to wash their hands before the delivery (3). In the studies conducted recently, compliance with hand hygiene among health workers was lower than 50% (4)(5)(6)(7). Although the methods and study groups of these studies are different from each other, it is a fact that hand-hygiene compliance rate is low globally (8).…”
Section: Introductionmentioning
confidence: 99%